Transient simulation and techno-economic assessment of a near-zero energy building using a hydrogen storage system and different backup fuels - Izadi, Ali; Shahafve, Masoomeh; Ahmadi, Pouria; Javani, Nader (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Proposing a cost-effective off-grid Hybrid Renewable Energy System (HRES) with hydrogen energy storage with a minimum CO2 emission is the main objective of the current study. The electricity demand of an office building is considered to be supplied by Photovoltaic Panels and wind turbines. The office building, modeled in Energy Plus and Open studio, has annual electricity consumption of 500 MWh electricity. 48.9% of the required electricity can be generated via renewable resources. Considering a system without energy storage, the remaining amount of electricity is generated from diesel generators. Hence, for reducing CO2 emission and fuel costs, a hydrogen energy storage system (ESS) is integrated into the system. Hydrogen ESS is responsible for supplying 38.6% of the demand electricity, which means that it can increase the energy supplying ability of the system from 48.9% to 87.5%. In addition to analyzing the application of the hydrogen storage system, the effect of four different kinds of fuel is considered as well. effects of Natural gas, Diesel, Propane, and LPG on the system's application are investigated in this study. Results indicate that natural gas emits less amount of CO2 compared to other fuels and also has a fuel cost of 3054 $/year, while hydrogen ESS is available. For the renewable system without ESS, the fuel cost rises to 10,266 $/year. However, liquid gas, Propane, and LPG have better performance in terms of CO2 emission and fuel cost, respectively.(c) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Off-grid energy system; Hybrid renewable energy system; Hydrogen energy storage; Diesel engine generator; Photovoltaic panel; WIND; OPTIMIZATION; BIOMASS; SOLAR; WATER; CELL; Chemistry; Electrochemistry; Energy & Fuels